2008
DOI: 10.1063/1.2904900
|View full text |Cite
|
Sign up to set email alerts
|

Nanotwins and phases in high-strain Pb(Mg1/3Nb2/3)1−xTixO3 crystal

Abstract: This work is a study of the thermal stability of ͑001͒-cut Pb͑Mg 1/3 Nb 2/3 ͒ 1−x Ti x O 3 ͑x = 0.30͒ single crystals before and after an electric ͑E͒-field poling by means of dielectric permittivity, hysteresis loop, domain structure, polarization current, and x-ray diffraction. An R͑R NT ͒-R͑R NT ͒ / T͑T NT ͒-T͑T NT ͒-C transition sequence was observed upon heating in the unpoled sample. R, R NT , T, T NT , and C are the rhombohedral, rhombohedral nanotwin, tetragonal, tetragonal nanotwin, and cubic phases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Nanotwin structures, which often cause broad XRD spectra, were also evidenced apparently in the ͑001͒ oriented PMN-30%PT crystal. 22 However, the recent in situ temperature-dependent XRD result of the ͑111͒-cut PMN-30%PT crystal did not show obvious imprint of nanotwin structure, implying that the elastic strain energy is smaller in the ͑111͒ oriented rhombohedral crystal. 23 Nanotwin structure seems to play an important role in the ͑001͒ oriented high-strain FE crystals while phase transition takes place because they can accommodate the spontaneous lattice distortion.…”
Section: Discussionmentioning
confidence: 91%
“…Nanotwin structures, which often cause broad XRD spectra, were also evidenced apparently in the ͑001͒ oriented PMN-30%PT crystal. 22 However, the recent in situ temperature-dependent XRD result of the ͑111͒-cut PMN-30%PT crystal did not show obvious imprint of nanotwin structure, implying that the elastic strain energy is smaller in the ͑111͒ oriented rhombohedral crystal. 23 Nanotwin structure seems to play an important role in the ͑001͒ oriented high-strain FE crystals while phase transition takes place because they can accommodate the spontaneous lattice distortion.…”
Section: Discussionmentioning
confidence: 91%
“…The R–M A phase transformation is predicted to be the minimum energy path of polarization rotation. The irregular shaped microdomains are possibly caused by rotating microdomains or nanocluster polarizations into alignment, which play an important role in PMN–PT single crystals because they can accommodate the spontaneous lattice distortion and minimize the elastic strain energy [23,24]. …”
Section: Resultsmentioning
confidence: 99%
“…62 Furthermore, we believe that higher mobility of these nano twins is responsible for giving rise to high strain energy density in MPB composition of NBT-BT. 63,64 Recently, in-situ TEM experiments under electrical biasing have also shown that in PZN, polarization reversal can occur by reorientation of nanoscale non-180 domain walls between monoclinic nanotwins. 65 The local crystallographic distortions in the MPB composition of NBT-BT can be justified from thermodynamic considerations as explained below.…”
Section: Resultsmentioning
confidence: 99%